Topping-Off Technology versus Posterior Lumbar Interbody Fusion in the Treatment of Lumbar Disc Herniation: A Meta-Analysis. (13th January 2020) - Wang, Wei; Sun, Xiangyao; Zhang, Tongtong; Sun, Siyuan; Kong, Chao; Lu, Shibao
Abstract : The treatment effects of topping-off technique were still controversial. This study compared all available data on postoperative clinical and radiographic outcomes of topping-off technique and posterior lumbar interbody fusion (PLIF). PubMed, EMBASE, and Cochrane were systematically reviewed. Variations included radiographical adjacent segment disease (RASD), clinical adjacent segment disease (CASD), global lumbar lordosis (GLL), visual analogue scale (VAS) of back (VAS-B) and leg (VAS-L), Oswestry disability index (ODI), Japanese Orthopaedic Association (JOA) score, duration of surgery, estimated blood loss (EBL), reoperation rates, and complication rates. Sixteen studies, including 1372 cases, were selected for the analysis. Rates of proximal RASD (P = 0.0004 ), distal RASD (P = 0.03 ), postoperative VAS-B (P = 0.0001 ), postoperative VAS-L (P = 0.02 ), EBL (P = 0.007 ), and duration of surgery (P = 0.02 ) were significantly lower in topping-off group than those in PLIF group. Postoperative ODI after 3 years (P = 0.04 ) in the topping-off group was significantly less than that in the PLIF group. There was no significant difference in the rates of CASD (P = 0.06 ), postoperative GLL (P = 0.14 ), postoperative ODI within 3 years (P = 0.24 ), and postoperative JOA (P = 0.70 ) and in reoperation rates (P = 0.32 ) and complication rates (P = 0.27 ) between topping-off group and PLIF. The results confirmed that topping-off technique could effectively prevent ASDs after lumbar internal fixation. However, this effect is effective in preventing RASD. Topping-off technique is more effective in improving the subjective feelings of patients rather than objective motor functions compared with PLIF. With the development of surgical techniques, both topping-off technique and PLIF are safe.